The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/ijms22115648
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Autophagy in Rat Tail Static Compression-Induced Intervertebral Disc Degeneration and Notochordal Cell Disappearance

Abstract: The intervertebral disc is the largest avascular low-nutrient organ in the body. Thus, resident cells may utilize autophagy, a stress-response survival mechanism, by self-digesting and recycling damaged components. Our objective was to elucidate the involvement of autophagy in rat experimental disc degeneration. In vitro, the comparison between human and rat disc nucleus pulposus (NP) and annulus fibrosus (AF) cells found increased autophagic flux under serum deprivation rather in humans than in rats and in NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…Yurube T et al [3] observed in vivo autophagy impairment in NP notochordal cells and apoptosis induction in NP non-notochordal cells under unphysiological mechanical loading-induced experimental disc degeneration of rat tails, supporting the interpretation that autophagy could protect notochordal cell homeostasis through limiting apoptosis in the disc NP.…”
Section: Degenerative Disc Diseasementioning
confidence: 85%
“…Yurube T et al [3] observed in vivo autophagy impairment in NP notochordal cells and apoptosis induction in NP non-notochordal cells under unphysiological mechanical loading-induced experimental disc degeneration of rat tails, supporting the interpretation that autophagy could protect notochordal cell homeostasis through limiting apoptosis in the disc NP.…”
Section: Degenerative Disc Diseasementioning
confidence: 85%
“…In addition, in an AT-1 transgenic mouse model of progeria, increased transport of cytosolic acetyl‐CoA into the ER lumen and blockade of ER autophagic recycling were found to be closely linked to defective ER-phagy, and functional restoration of ER-phagy rescued the aging phenotype in total and extended the lifespan 48 . Furthermore, it has been established that autophagy is crucial for the maintenance of IVD homeostasis and that autophagy impairment is directly involved in the induction of irregular notochordal cell disappearance, nonnotochordal cell apoptosis and senescence 49 51 . Therefore, we investigated the effects of FAM134B-mediated ER-phagy on cell functionality and survival in human NP cells under nutrient starvation conditions and found that FAM134B-mediated ER-phagy was activated in response to ND and that FAM134B knockdown significantly aggravated ND-induced apoptosis and senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Intervertebral disc degeneration (IVDD) is a key recognizable fact for back and neck pain in adults leading to decrease quality life sometimes making disable (1)(2)(3)(4). IVDD is a pathological and physiological process that can be chronic and progressive (1).The disease is of widespread prevalence .…”
Section: Introductionmentioning
confidence: 99%
“…About 80% of the mature individuals would be subjected to back and neck pain at any stages in their life (2,5,6). Intervertebral disc (IVD),an important element which can tolerate various kinds of load depending on the intensity of load (7).Many studies have been conducted, where mentioned excessive external stress, hereditary disease, obesity and aging are most common enhancer of IVDD (1,3,6,8). However, mechanical stimulus is another important key contributor for IVDD, when it exceeds tolerable margin of load baring elements (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation